TEACHERS READING STATUS OF LITERATURE RECOMMENDED BY THE MINISTRY OF NATIONAL EDUCATION - Ahmet Oguz AKÇAY (Fırat University, 2019)
In today's information age, book reading habit plays a key role to gain of knowledge, the inquiry of thought, and for social skills. Teachers have important roles to be a role model for their students in the way of reading habits. The Teaching Turkish Education Program published by the Ministry of National Education in 2005 is aimed to be gained "the habit of reading and writing" to the students. In this context, the General Directorate of Teacher Training and Development has recommended 37 books and 30 films to the teachers to read during the summer vacation and critically discuss with their colleagues. The purpose of this study is to analyze teachers attitudes towards reading recommended books by the Ministry of National Education. The survey was conducted to collect data and, 164 teachers completed the survey. The findings show that a significant difference was found between the Turkish/Social Sciences teachers and the Elementary Education teachers and Computer Educatıon and Instructıonal Technology teachers about the time spending for reading books in daily life, and reading of recommended books by the Ministry of National Education. Also, there was not a significant difference for gender and experience for the time spending for reading the book in daily life between the daily reading time and the sex of the participants.